Strategic Positioning Of Private Banks In Syria During The Turbulent Business Environment - Habib, Ghaith (2015)
The war in Syria has been taking place for over three years (2011 to 2014), and the private banking sector had to stop most of its commercial and retail lending as well as offering financing activities (Letter of Credits and Letter of guarantees) in US dollars. In addition, the European Union and the US government have had imposed sanctions on the central bank and the state-owned banks. Moreover, several major shareholders in the private banking sector were personally under similar sanctions, and most of their assets were frozen in their overseas accounts. Thus they had to sell their shares and others had to resign as board members. Lastly, and the most negative factors is the increasing amount of non-performing loans, where many of the clients’ factories and businesses are located in the rural areas where a high level of violence was taking place. Thus, these factories and business locations were closed and a major part of them were completely destroyed. Not to mention the fact that Aleppo (the second largest city and the capital industrial one) was occupied by Islamic radicals coming from the North, and most of the industrial factories equipments were stolen and shipped to Turkey. All these elements have summed the large portion of the non-performing loans which have increased by 250% , and it was hard for the loan recovery units at the banks to raise law suits since court houses were not operating regularly, and the clients were either fleeing out of the country or simply unable to pay. In total, all of these elements have lead to a decline in the profitability of the banks for three consecutive years, and a threat for their current position and sustainability.